MODEL PEMBELAJARAN DISCOVERY SECARA BLENDED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATERI ASAM DAN BASA - SUKEMI SUKEMI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
A teacher needs to strengthen a learning model that has been implemented by combining face-to-face learning (PTM) with online learning. This learning model is called blended learning. To find out the learning outcomes of the cognitive and psychomotor domains with this learning model, we conducted classroom action research with the title: Application of blended learning discovery learning model using Google Classroom to improve learning outcomes of acid and base material for class XI IPA SMA Negeri 3 Metro in the academic year 2021/ 2022. This research is classroom action research. The procedure is: the research is carried out in 3 cycles and each cycle has 4 stages of action, namely: planning, implementing, observing or testing, then reflection. An indicator of research success is an increase if learning outcomes are compared between cycles. The learning outcomes that we compare are the average and percentage of class completeness (PK) in the cognitive and psychomotor domains. The results of our study indicate that this class action can improve cognitive learning outcomes from an average of 53 to 70. The score of 70 is quite good. Class actions can also increase the Class Completeness Percentage (PK) from 23% to 53%. Psychomotor learning outcomes show that there is a percentage of class completeness (PK) equal to 99%, this number includes very good criteria. ABSTRAKSeorang guru perlu memperkuat suatu model pembelajaran yang telah dilaksanakannya dengan cara menggabungkan antara Pembelajaran Tatap Muka (PTM) dengan pembelajaran daring. Model pembelajaran demikian ini disebut dengan blended learning. Untuk mengetahui hasil belajar ranah kognitif dan ranah psikomotorik dengan model pembelajaran ini maka kami melakukan penelitian tindakan kelas dengan judul: Penerapan model pembelajaran discovery secara blended learning menggunakan Google Classroom untuk meningkatkan hasil belajar materi asam dan basa kelas XI IPA SMA Negeri 3 Metro tahun pelajaran 2021/2022. Penelitian ini adalah penelitian tindakan kelas. Prosedurnya adalah: penelitian dilaksanakan sebanyak 3 siklus dan tiap siklus mempunyai 4 tahap tindakan, yaitu: perencanaan, pelaksanaan, observasi atau tes, lalu refleksi. Indikator keberhasilan penelitian adalah adanya kenaikan jika hasil belajar dibandingkan antar siklus. Hasil belajar yang kita bandingkan adalah rata-rata dan persentase ketuntasan kelas (PK) ranah kognitif dan ranah psikomotor. Hasil penelitian kami menunjukkan bahwa tindakan kelas ini dapat meningkatkan hasil belajar ranah kognitif dari rata-rata 53 dapat meningkat menjadi 70. Angka 70 masuk kriteria cukup baik. Tindakan kelas juga dapat meningkatkan Persentase Ketuntasan Kelas (PK) dari 23 % menjadi 53 %. Hasil belajar ranah psikomotor menunjukkan adanya persentase ketuntasan kelas (PK) sama dengan 99% angka ini termasuk kriteria sangat baik.